Clustering of asthma and related comorbidities and their association with maternal health during pregnancy: evidence from an Australian birth cohort - Ahmad, Kabir; Kabir, Enamul; Ormsby, Gail M; Khanam, Rasheda (My University, 2021)
The population-based classification of asthma severity is varied and needs further classification. This study identified clusters of asthma and related comorbidities of Australian children aged 12-13 years; determined health outcome differences among clusters; and investigated the associations between maternal asthma and other health conditions during pregnancy and the children's clustered groups.
BMC Public Health
Keywords: Asthma; Asthma related comorbidities; Cluster analysis; General well-being; Latent class analysis; Paediatric quality of life; Spirometry; Families and relationships; Health and wellbeing